FORMULASI SERUM NANOPARTIKEL EKSTRAK ETANOL KULIT BUAH KAKAO (Theobroma cacao L.) SEBAGAI ANTIOKSIDAN - Rahayu, Feri Kanti (Parapemikir : Jurnal Ilmiah Farmasi, 2025)
Antioxidants are compounds that are able to stop oxidation reactions so that they can inhibit cell damage in the body. Cocoa pods (Theobroma cacao L.) contain polyphenols and flavonoids that function as free radical antidotes. This study aims to determine whether ethanol extract of cacao fruit peel (Theobroma cacao L.) can be formulated as a nanoparticle serum preparation and has antioxidant activity. This research was conducted at the Pharmacognosy, Instrument, and Pharmaceutical Technology Laboratory of STIKes Ibnu Sina Ajibarang. This type of research is descriptive experimental, namely characterisation of ethanol extract of cacao fruit skin with UV-Vis spectrophotometry, preparation of serum nanoparticles; physical evaluation through organoleptic test, homogeneity, pH, viscosity and cycling test and antioxidant activity test with DPPH (1,1-diphenyl-2picrylhydrazyl) method. The results of nanoparticle characterisation obtained a maximum wavelength of 430 nm with an absorbance of 0.353 at a concentration of 5 ppm showed a particle size of 50-60 nm. The results of the physical evaluation of the preparation showed that all formulations F0, FI, FII, and FIII met the requirements of the physical properties test and stability test, so it can be stated that cocoa fruit peel extract can be formulated as a nanoparticle serum preparation. The antioxidant activity test results of F0, FI, FII, and FIII were 5.12 ppm; 4.62 ppm; 4.28 ppm; 3.16 ppm, respectively. So it can be concluded that the most effective nanoparticle serum preparation is FIII with 3% extract concentration.